2019
DOI: 10.1093/femsec/fiz105
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen suppression by microbial volatile organic compounds in soils

Abstract: There is increasing evidence that microbial volatile organic compounds (mVOCs) play an important role in interactions between microbes in soils. In this minireview, we zoom in on the possible role of mVOCs in the suppression of plant-pathogenic soil fungi. In particular, we have screened the literature to see what the actual evidence is that mVOCs in soil atmospheres can contribute to pathogen suppression. Furthermore, we discuss biotic and abiotic factors that influence the production of suppressive mVOCs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 106 publications
0
37
0
Order By: Relevance
“…The overall aim of sustainable farming is to cut down the use of pesticides (European Commission, 2017). The greater reliance on the beneficial functions and ecosystem services provided by the soil microbiome is a promising approach forward (Sipilä et al, 2012;Constanzo and Barberi, 2014;de Boer et al, 2019). Disease suppressive soils, through the competitive activity of the non-pathogenic residents of the total soil microbiota (general suppression) or the antagonistic capabilities of specific groups of microorganisms (specific suppression), are able to reduce the occurrence or severity of diseases caused by soilborne phytopathogens (Weller et al, 2002;Dignam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall aim of sustainable farming is to cut down the use of pesticides (European Commission, 2017). The greater reliance on the beneficial functions and ecosystem services provided by the soil microbiome is a promising approach forward (Sipilä et al, 2012;Constanzo and Barberi, 2014;de Boer et al, 2019). Disease suppressive soils, through the competitive activity of the non-pathogenic residents of the total soil microbiota (general suppression) or the antagonistic capabilities of specific groups of microorganisms (specific suppression), are able to reduce the occurrence or severity of diseases caused by soilborne phytopathogens (Weller et al, 2002;Dignam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The complex interplay of soil suppressiveness cannot simply relate to a single microbial taxon or group (de Boer et al, 2007;Legrand et al, 2019). The majority of rhizobacterial taxa indicative of the suppressiveness status of the soil may differ when comparing different types of suppressive soils or even different soils suppressive to a same phytopathogen (de Boer et al, 2019;Wang and Li, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microbial volatile organic compounds (VOCs) have come into the limelight as potential candidates to substitute the outlawed chemical fumigants (De Boer et al, 2019). Indeed, their physiochemical characteristics such as low boiling point, high vapor pressure and low molecular weight (<300 Da) (Piechulla et al, 2017), their activity in both gas and liquid phases and ability to re-evaporate after diffusing through water-filled pores, allow microbial VOCs to move easily through the soil pores network (Effmert et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to the lower types and concentrations of phenolic acids in rhizosphere soil of wild R. pseudostellariae. Previous studies have shown that the volatiles of the bacterial community had strong negative effects on the assembly of soil fungal colonizers (Li et al, 2020), and competitive interactions within soil beneficial bacterial communities could trigger the production of mVOCs (volatile organic compounds) that suppressed plant pathogenic fungi (De Boer et al, 2019). Our study implied that complex plantmicrobe interactions may have suppressed host-specific pathogen accumulation in the rhizosphere of wild R. pseudostellariae.…”
Section: Wild R Pseudostellariae Supports Beneficial Microbes But Sumentioning
confidence: 54%